Strategi Komunikasi Pemasaran Wisata Edukasi Seni Kampung Dongeng Jombang dalam Membangun Brand Awareness - Alfiana, Mita; M.A., Tatak Setiadi, (Universitas Negeri Surabaya, 2025)
Kampung Dongeng or what is usually called (KaDo) is one of the arts education tourism destinations among other tourist destinations in Jombang Regency which provides activities that are different from one another. There needs to be a form of interaction so that marketing goals and objectives can be achieved effectively and efficiently through marketing communications. The aim of the research is to find out the marketing communication strategy carried out by Kampung Dongeng Jombang in building brand awareness. The research uses descriptive qualitative methods with a case study approach. Data collection was carried out through in-depth interviews, observation, documentation and literature study. The research results found that the Kampung Dongeng Jombang focuses on 5 aspects, namely promotion through publicity and public relations, Event and Experience, Personal Selling, Internet, And Word of Mouth And Product, price, people, Physical Evidance which supports promotions. The Marketing Communication Strategy to build brand awareness carried out by Kampung Dongeng Jombang Regency was successful and made the people of Unware begin to recognize and be aware of the educational tourism of Kampung Dongeng Jombang.